Effects of Antitumor Drug Sorafenib on Chick Embryo Development. Issue 7 (17th April 2015) - Cheng, Yi‐Sen; Wang, Xiao‐Yu; Wang, Guang; Li, Yan; Chen, Yue‐Lei; Chuai, Man‐li; Lee, Kenneth Ka Ho; Ding, Xiao‐Yan; Yang, Xue‐song
ABSTRACT Sorafenib has been used as an oral anti‐cancer drug because of its ability to inhibit tumor growth. However, the pharmacological effect of sorafenib is still the lack of in vivo experimental evidence. Tumor and embryonic cells share some similar features, so we investigated the effects of sorafenib on the development of gastrulating chick embryos. We found that sorafenib exposure was markedly attributed to the number of embryonic cell in proliferation and apoptosis. We also detected sorafenib significantly interfered with epithelial‐mesenchymal transition (EMT). Furthermore, sorafenib treatment impaired the production and migration of neural crest cells. Anat Rec, 298:1271–1281, 2015. © 2015 Wiley Periodicals, Inc.